Respuesta :

Answer:

Explanation:

We can factor the numerator and denominator as;

(

x

2

)

(

x

1

)

2

x

(

x

1

)

We can now cancel common term in the numerator and denominator:

(

x

2

)

(

x

1

)

2

x

(

x

1

)

x

2

2

x

However, we cannot divide by

0

so we must exclude:

2

x

=

0

x

=

0

and

x

1

=

0

x

1

x

2

3

x

+

2

2

x

2

2

x

=

x

2

2

x

Where:

x

0

and

x

1

Or

x

2

3

x

+

2

2

x

2

2

x

=

x

2

x

2

2

x

=

1

2

1

x

Where:

x

0

and

x

1

Step-by-step explanation:

Answer:

[tex](2x^2+3x)+(4x^2-7)[/tex] =

[tex]6x^2+3x-7[/tex]

ACCESS MORE